IMPLEMENTASI KRITERIA COMMUNITY-BASED TOURISM ASEAN: STUDI KASUS PADA DESA WISATA ALAMENDAH - Nirwani, Ayulia; Azizah, Nur; Fauzany, Riffka; Keizer, Hendriady de (Jurnal Perhotelan dan Pariwisata, 2023)
The concept of Community Based Tourism (CBT) is one implementation of sustainable tourism that accommodates various factors involved in it. CBT is directed towards developing the economic, environmental, and social sectors, guided by government policies. In its development, CBT adheres to standardized practices. These standards are underpinned by The ASEAN Community-based Tourism, which divides them into eight criteria and one additional, including community ownership and management, contribution to social well-being, conserving and improving the environment, encouraging interaction between the local community and guests, provision of quality tourism services and guides, quality of food and beverages, quality of accommodations, the performance of friendly tour operators, and the utilization of technology. This research analyzes the implementation of these standards in the Alamendah tourist village. Based on the research findings, it is evident that the Alamendah tourist village has implemented the ASEAN Community-based Tourism criteria appropriately. Keywords: Community-based tourism, ASEAN CBT, Rural Tourism